2021
DOI: 10.3390/ijerph182111187
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Disaster Risk—An Overview

Abstract: The role of natural disaster adaptation is increasingly being considered in academic research. The Paris Agreement and Sustainable Development Goal 13 require measuring the progress made on this adaptation. This review summarizes the development stages of adaptation, the multiple attributes and analysis of adaptation definitions, the models and methods for adaptation analysis, and the research progress of natural disaster adaptation. Adaptation research methods are generally classified into two types: case ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 107 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…Farmers who possess the ability to perceive risks can better understand the characteristics and extent of encountered hazards, enabling them to respond effectively in their future behavior. In general, farmers tend to manage injury events and associated risks through adaptive decision-making, drawing from previous injury experience ( 78 ). Several researchers have observed that farmers with a history of serious injuries are less likely to experience subsequent injuries among workers ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Farmers who possess the ability to perceive risks can better understand the characteristics and extent of encountered hazards, enabling them to respond effectively in their future behavior. In general, farmers tend to manage injury events and associated risks through adaptive decision-making, drawing from previous injury experience ( 78 ). Several researchers have observed that farmers with a history of serious injuries are less likely to experience subsequent injuries among workers ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…There needs to be a strategy to adapt to landslide disaster conditions so that students can carry out the learning process more optimally. According to Jia, Chen, & Du [13], humans need adaptation to maintain relationships with fellow humans to have ideal conditions in relation to environmental changes. Tri's opinion is in line with the opinion of Sanjatmiko, et al [14] who states that adaptation is a human effort to achieve certain goals or to face changing environmental and social conditions in order to survive.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review indicates that various methods for disaster adaptation have been proposed. A recent review highlighted 2 critical dimensions of disaster adaptation: the spatial scale of adaptation and the nature of adaptive behavior [ 5 ]. The concept of disaster adaptation also pertains to the recovery, balance, and management of adaptations to changes in the natural environment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%